Hide and Seek: How Lyme Disease Spirochetes Overcome Complement Attack - Kraiczy, Peter (Frontiers in Immunology, 2016)
Overcoming the first line of the innate immune system is a general hallmark of pathogenic microbes to avoid recognition and to enter the human host. In particular, spirochetes belonging to the Borrelia burgdorferi sensu lato-complex have developed various means to counter the immune response and to successfully survive in diverse host environments for a prolonged period of time. In regard to complement resistance, Borrelia utilize a plethora of immune evasion strategies involves capturing of host-derived complement regulators, terminating complement activation as well as shedding of cell-destroying complement complexes to manipulate and to expeditiously inhibit human complement. Owing to their mode of action, the interacting surface-exposed proteins identified among B. burgdorferi sensu stricto (s.s.), B. afzelii, B. spielmanii, and B. bavariensis can be classified into at least two major categories, namely molecules that directly interfere with distinct complement components including BBK32, CspA, BGA66, BGA71, and a CD59-like protein or molecules which indirectly counteract complement activation by binding various complement regulators such as Factor H, Factor H-like protein 1 (FHL-1), Factor H-related proteins FHR-1, FHR-2, or C4Bp. The latter group of genetically and structurally unrelated proteins has been collectively referred to as “complement regulator-acquiring surface proteins” and consists of CspA, CspZ, ErpA, ErpC, ErpP, and the as yet unidentified protein p43. This review focuses on the current knowledge of immune evasion mechanisms exhibited by Lyme disease spirochetes and highlights the role of complement-interfering, infection-associated molecules playing an important part in these processes. Deciphering the immune evasion strategies may provide novel avenues for improved diagnostic approaches and therapeutic interventions.